Aquamaniles in Lithuania and Europe - Ardavičiūtė, Skaistė (Archaeologia Lituana, 2016)
The main aim of this paper is to establish a better understanding, dating and recognition of aquamaniles found in Lithuania by comparing the context and dating of metal aquamaniles with their Western European counterparts. Aquamanile is anthropomorphic or zoomorphic vessel, which was used to pour water on hands in order to wash them. Aquamaniles were made in Islamic world and in Western Europe in late medieval times using metal alloys (copper, brass) or clay and are in many different forms, ranging from lions, knights on horseback, mythical beasts to human busts. The main function of aquamanile was to pour water on the hands for the washing. Aquamaniles were used in both sacral and secular contexts, but it is still debatable in which they were started to be used first. Although the term aquamanile is now widely used to define a zoomorphic or anthropomorphic vessel used to pour water on hands, sometimes the old term, namely, urceolus, or the old definition, defining that aquamanile was a basin or a vessel to hold holy water, can be found. For example, in the Wawel cathedral catalogue aquamanile in the form of lion is called urceolus (Wawel, 2000, p. 259). Aquamaniles are virtually universal with examples coming from late Roman, early Byzantine and Islamic cultures. Through commercial trade, plunder and diplomatic gift exchange metal aquamaniles reached Western Europe. However, the most important factor which stimulated the emergence of metal aquamaniles in the twelfth century in Western Europe was cultural exchange. Metalworkers adopted a new metalworking technique (lost wax or cire perdue), which enabled them to cast hollow three-dimensional objects, metal aquamaniles being their first creations (Dandridge, 2008, p. 78). However, the forms of Islamic aquamaniles were not copied by Western metalworkers, but rather adapted to fit in with Western culture (Barnet, 2006; Dandridge, 2008). For example, there were no knight on horseback aquamaniles in Islamic culture, whereas such form was the second most popular in Western Europe during late medieval times. The main metalworking centres where many surviving aquamaniles were created between the 12th and the end of the 14th century were Lower Saxony and Lotharingia. From the 15th century onwards a new centre emerged in Nuremberg (Southern Germany). O. Falke and E. Meyer were the first to attribute nearly 350 metal aquamaniles to the three major stylistical groups – Romanesque (from the 12th to the first half of the 13th century), Early Gothic (second half of the 13th century) and Late Gothic (the beginning of 14th century to the 16th century) (Falke, Meyer, 1935, p. 38). Romanesque aquamaniles usually are quite stubby and rarely look like a real animal. Early Gothic aquamaniles are bigger and more slender than the Romanesque and usually have a collar around their necks, round ears and big almond shaped eyes. Late Gothic aquamaniles are realistic in form with later examples becoming very big and having flame-tails and a spiggot in their chests. Two aquamaniles were found in Lithuania. One is in the form of a lion and was found in Bartkuškis (Širvintos district). O. Falke and E. Meyer mention that this aquamanile was found in Reval (Tallin), but in V. P. Darkevich and B. R. Vitkauskienė papers it is written that it was found in Vilnius governorate and Bartkuškis (Falke, Meyer, 1935, p. 211; Даркевич, 1966, p. 42; Vitkauskienė, 2001, p. 691). Although all the references were checked, it is still unclear where the aquamanile was really found. Another aquamanile, to be precise, its fragments, were found in Vilnius Lower Castle. It was also in the form of a lion. However, the vague context and small fragments make it difficult to date the aquamanile. The building in which the fragments were found was built in the second half of the 13th century, but due to intensive ground moving works it is possible that the aquamanile fragments got in from the later layers. After comparing aquamanile fragments from Vilnius Lower Castle with other aquamaniles found in Western Europe, it was possible to date its manufacture date to the end of the 13th century – first half of the 14th century. Aquamanile was made in one of the Lower Saxony metalworking workshops.